GAMBARAN PENGETAHUAN BAHAYA ROKOK ELEKTRIK (VAPE) PADA REMAJA PUTRI DI KOTA MEDAN - Kiara Aulia Pelawi; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
The dangers of smoking are an unresolved problem. Many of these individuals ignore the dangers of smoking for health. Some of them smoke because of environmental influences or friendship styles, then there are also those who smoke because of pressure or stress, not a few are just because of trying. Especially now that there are electronic cigarettes where smokers switch to electronic cigarettes for the reason that they can be separated from smoking habits. But in reality, e-cigarettes are just as dangerous for health. The phenomenon that exists today, many young women become users of electronic cigarettes and do not know the dangers of electronic cigarettes. The study aims to determine the relationship between knowledge and perception of electronic cigarette (vape) use in adolescent girls in Medan City. This type of research is quantitative research with a descriptive survey approach. Sampling technique using accidental sampling approach. Data was collected using questionnaires through google forms. The results of statistical tests showed p value =0.278 > α (0.05), there was no relationship between knowledge of the dangers of electronic cigarettes (vape) in women's reamaja. The good and bad behavior of a person in the field of health depends on the level of knowledge possessed. The lower the knowledge of adolescents about the dangers of electronic cigarettes, the more potential to become permanent smokers of electronic cigarettes. Efforts to reduce the use of e-cigarettes among adolescents can be done by increasing their knowledge about the dangers of e-cigarettes through health promotion, with health counseling by Puskesmas and the Health Office.